Physician payment models and cardiac imaging in patients at low cardiovascular risk: A population-based cohort study in Alberta, Canada - Yewande Kofoworola Ogundeji; Amity E. Quinn; Derek S. Chew; Flora Au; Stephen B. Wilton; Matthew T. James; Marcello Tonelli; Braden J. Manns (PLoS ONE, 2025)
Background Many factors beyond patient need influence the care that patients receive, including the way physicians are paid, and how services are delivered. In Alberta, outpatient non-invasive cardiac imaging (“cardiac imaging”) is paid for publicly but performed at private, for-profit (investor/physician owned) facilities. We investigated patient, physician, and geographic factors associated with cardiac imaging in patients at low cardiovascular risk seeing specialist physicians in Alberta, Canada. Methods This was a population-based retrospective cohort study using administrative health data from Alberta, Canada, where nearly all outpatient cardiac imaging is done at privately for-profit community-based facilities. We used administrative health data to identify a cohort of adult (aged ≥18 years) patients at low cardiovascular risk who were assessed by a cardiologist or internal medicine specialist for a new outpatient visit for a cardiac-related reason between April 1, 2011 and December 30, 2019 in Alberta. The primary outcome was cardiac imaging. Explanatory variables included patient and physician characteristics, including payment model (fee for service (FFS) or salary-based), and geography. We used multilevel, multivariable logistic regression models to measure the association between these factors and cardiac imaging. Results We identified 398,095 patients at low cardiovascular risk, of whom 27.5% received at least one cardiac imaging test. Compared to those seen by FFS cardiologists (and controlling for patient and geographic differences), patients seen by salary-based internal medicine specialists had the lowest odds of receiving cardiac imaging (OR=0.055, P < 0.001, CI 0.036–0.086), followed by those seen by FFS internal medicine specialists (OR=0.010, P < 0.001, CI 0.068–0.14), and salary-based cardiologists (OR=0.27, P < 0.001, CI 0.16–0.45). Findings were robust across multiple sensitivity analyses. Conclusions Physician payment models and specialty are strongly associated with non-invasive cardiac imaging among patients at low cardiovascular risk.